Experience of SARS‐CoV‐2 infection in two kidney transplant recipients living with HIV‐1 infection. Issue 2 (22nd December 2020) - Chowdary, Prashanth; Shetty, Shraddha; Booth, John; Khurram, Muhammad Arslan; Yaqoob, Magdi; Mohamed, Ismail Heyder
Abstract: There is still no consensus on the optimal management of COVID‐19 within the general population due to the emerging evidence base. High‐risk groups, including kidney transplant recipients living with HIV present unique additional challenges. Here we discuss two kidney transplant recipients living with HIV with SARS‐CoV‐2 infection and their clinical course, and review the existing literature for this subset of challenging patients.